Neuroglobin Plays a Protective Role in Arsenite-Induced Cytotoxicity by Inhibition of Cdc42 and Rac1GTPases in Rat Cerebellar Granule Neurons - Xiaona Liu (Cellular Physiology and Biochemistry, 2015)
Background and Aims: We have previously shown that neuroglobin (Ngb) expression can be regulated by sodium arsenite (NaAsO2) exposure in rat cerebellar granule neurons (CGNs). However, the precise molecular mechanisms of Ngb action are largely unknown. Ras homolog (Rho) guanosine triphosphatases (Rho GTPases) are involved in the regulation of a number of cellular processes, including cell cytotoxicity. It has been reported that Ngb can act as a guanine nucleotide dissociation inhibitior (GDI) role to inactivate Rho GTPases. Therefore, we investigated Rho GTPases activation induced by NaAsO2 exposure in rat CGNs and effects of Rho GTPases activation on the cells. We also investigated the role of Ngb in this process. Methods: Primary cultures of CGNs were prepared from 7-day-old Wistar rat pups. The cytotoxic effects of NaAsO2 on CGNs were evaluated using the Cell Counting Kit-8 assay and TUNEL staining. RNA interference technology was used to silence Ngb, and the subsequent effects were evaluated by quantitative RT-PCR and Western blot. Cdc42 and Rac1 activation were measured by pull-down assay and Western blot. Results: NaAsO2 induced cytotoxicity in rat CGNs, increased GTP-bound form of Cdc42 and Rac1 GTPases in the cells. Furthermore, inhibition of Cdc42 or Rac1 activity using the inhibitor ZCL278 or NSC23766 decreased apoptosis and increased cell viability in the cells exposed to NaAsO2. Using siRNA-mediated knockdown, we show that NaAsO2-induced cytotoxicity was exacerbated, activation of Cdc42 (GTP-Cdc42) and Rac1 (GTP-Rac1) was increased in Ngb RNA silencing cells. Conclusions: cytotoxic effects of NaAsO2 on rat CGNs is induced at least partly by Cdc42 and Rac1 activation, and Ngb can inhibit Cdc42 and Rac1 activation to play protective role in rat CGNs exposed to NaAsO2.